Optoelectronic tracking system for shooting simulator - tests in a virtual reality application - Maciejewski, Marcin; Piszczek, Marek; Pomianek, Mateusz; Pałka, Norbert (Photonics Letters of Poland, 2020)
We present test results of an authorial tracking device developed in the SteamVR system, optimized for use in a missile launcher shooting simulator. Data for analysis was collected using the virtual reality training application, with the launcher set on a stable tripod and held by a trainee who executed two scenarios with static and movable targets. The analysis of experimental data confirms that the SteamVR system together with the developed tracker can be successfully implemented in the virtual shooting simulator. Full Text: PDF References D. Bogatinov, P. Lameski, V. Trajkovik, K.M. Trendova, "Firearms training simulator based on low cost motion tracking sensor", Multimed. Tools Appl. 76(1) (2017) CrossRef D.C. Niehorster, L. Li, M. Lappe, "The Accuracy and Precision of Position and Orientation Tracking in the HTC Vive Virtual Reality System for Scientific Research", Iperception. 8(3) (2017) CrossRef A. Yates, J. Selan, POSITIONAL TRACKING SYSTEMS AND METHODS. US20160131761A1, (2016) DirectLink P. Caserman, A. Garcia-Agundez, R. Konrad, S. Göbel, R. Steinmetz, Virtual Real. 23(2) (2019) 155-68. CrossRef